Pengembangan LMS Moodle Terintregasi Plugin Coderunner Untuk Mendukung Hasil Belajar Siswa Kelas X SMKN 2 Surabaya - Anindhita Rahmadini; Elvira Wardah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Limited computer laboratory facilities and the absence of independent practice-based digital learning media in Informatics classes at SMKN 2 Surabaya became the starting point for this research. The study describes the development process and feasibility level of a Moodle Learning Management System (LMS) integrated with the CodeRunner plugin for the Algorithm and Programming element, while also examining differences in student learning outcomes. Research and Development (R&D) following the ADDIE model was applied together with a Quasi-Experimental design in the form of a Nonequivalent Control Group Design. Tenth-grade Software Engineering (RPL) students at SMKN 2 Surabaya served as the research subjects, with class X RPL 2 acting as the experimental group and class X RPL 1 as the control group. Data were collected through tests and questionnaires, drawing on expert validation sheets, pre-test and post-test items, and the User Experience Questionnaire (UEQ). Descriptive feasibility analysis and the Man Whitney U-Test were used to analyze the data. Expert validation placed the media in the highly feasible category for classroom use. The Independent Sample T-Test further showed a significant difference in post-test results between the experimental and control classes, with the auto-checker and automatic feedback features in the experimental class driving more optimal learning gains. Student responses captured through the UEQ likewise leaned positive regarding the media's usability. Taken together, these findings indicate that the CodeRunner-integrated Moodle LMS is valid and effective for improving student learning outcomes, and Informatics teachers are encouraged to adopt this media to support independent programming practice.